Função luteal inicial em ovelhas submetidas a pneumoperitônio durante o estro - Zielinski, Caroline Flores (2008)
Ewes submitted to artificial insemination by laparoscopy have an increase in serum cortisol levels. Pain induced by pneumoperitoneum appears to be the cause of such increase and may be related to the low conception rates of the technique. The objective of this study was to investigate progesterone levels in ewes following pneumoperitoneum during estrus. One hundred nineteen ewes were synchronized with vaginal pessaries for 12 days. After pessary removal animals were exposed to testosterone primed teaser whethers (GR) or rams (GCa), marked ewes were immobilized in a insemination cradle and submitted (GT) or not to pneumoperitoneum (GC). Blood samples were collected on days three, six and nine after treatment for progesterone (P4) analysis. No interaction was found between P4 and GCa, GR or between P4 and GT and GC. P4 values were higher on GCa on days three and six than in GR (P<0.0001). There were no differences in pregnancy rates between GT and GC in ram served ewes, nor interaction between pregnancy and P4 levels on days three, six and nine. Pregnancy rates were low, 43 and 64% for GT and GC groups respectively. It is concluded that pneumoperitoneum per se on the day of estrus does not affect subsequent P4 levels in sheep.